Reduction of Postoperative Nausea and Vomiting Induced by Spinal Anesthesia: Peppermint and Lavender Aromatherapies as Complementary Therapies - Taufan Arif; Maria Diah Ciptaningtyas; Navalia Nailin Mudviyanti; Fitriana Kurniasari Solikhah (Folia Medica Indonesiana)
Highlights: 1. This study provides insight into the effectiveness of peppermint and lavender aromatherapies in reducing postoperative nausea and vomiting in patients following spinal anesthesia. 2. Aromatherapies with peppermint and lavender administered three times within six hours have demonstrated potential as an easy-to-apply intervention that reduces postoperative nausea and vomiting. 3. In terms of effectiveness, however, peppermint aromatherapy exhibits a higher effectiveness in reducing nausea and vomiting compared to lavender aromatherapy.